"My Javelin Throw" Android-based Javelin Throw Learning Application - Ibnu Fatkhu Royana; Deni Wahyu Jumawan; Bertika Kusuma Prastiwi; Pandu Kresnapati; Tubagus Herlambang; Donny Anhar Fahmi; Muh Isna Nurdin Wibisana; Danang Aji Setyawan; Utvi Hinda Zhannisa (Advance Sustainable Science Engineering and Technology, 2023)
This research is motivated by the need for a new learning model with different and engaging learning media, particularly in javelin throwing education. The aim of this research is to create an Android-based learning media for javelin throw. The method in this research is Research and Development (R&D). The subjects and location of this research are 11th-grade students of SMA Negeri 1 Bantarbolang, Pemalang Regency. In the small-scale research, the sample consists of 21 11th-grade students, while in the large-scale research, the sample consists of 272 11th-grade students. The data collection technique used is a questionnaire as the instrument. The quantitative data analysis technique in this research utilizes descriptive statistical analysis. The final validation results from media experts indicate that all aspects are rated as "Good" with a score of 78%. Meanwhile, the final validation from subject matter experts indicates that all aspects are rated as "Excellent" with a score of 82%. According to the data analysis results in the small-scale trial, the percentage obtained is 86.17%.